Evaluation of the Effect of Single Bolus Dose of Intravenous Dexmedetomidine in Spinal Anaesthesia for Lower Limb Surgeries - Paudel, Bandana; Rai, Pramod; Tiwari, Robins; Gautam, Sanjay; Paudel, Sumitra; Shubham, - (Birat Journal of Health Sciences, 2020)
Introduction: The use of intrathecal adjuvants in spinal anaesthesia in enhancing and prolonging it’s action has been well established and is widely used for surgery below the umbilicus. Dexmedetomidine, a selective α2A receptor agonist is a suitable adjuvant due to its selective activity. Objectives: To evaluate the effect of a single bolus dose of intravenous dexmedetomidine as an adjuvant in cases undergoing lower limb surgeries under spinal anaesthesia. Methodology: One hundred patients posted for lower limb surgery under spinal anaesthesia with hyperbaric bupivacaine, were equally divided into two groups. In group D, in addition to spinal, intravenous dexmedetomidine 0.5mcg/kg over 10 min was given whereas group C patients received spinal and intravenous normal saline . Results: The onset of sensory and motor block was faster in group D (2.09 ± 0.71 min, 3.18 ± 1min)compared to group C (3.5 ± 0.82 min, 6.19 ± 1.87 min) which was statistically significant . The duration of sensory and motor block was also significantly prolonged in Group D (174.5 ± 14.04 min, 133.4 ± 10.42 min) as compared to Group C(138.2 ± 11.51 min, 120.4 ± 8.8 min).The duration of analgesia in Group D (225.3 ±20.11 min)was prolonged when compared to Group C (168.3 ± 15.11). Conclusion: Intravenous dexmedetomidine as a single bolus dose before spinal anaesthesia can fasten the onset of sensory and motor block, prolongs the duration of sensory and motor block and also increased the duration of analgesia.